Evidence for genetic heterogeneity between clinical subtypes of bipolar disorder - Charney, A W; Ruderfer, D M; Stahl, E A; Moran, J L; Chambert, K; Belliveau, R A; Forty, L; Gordon-Smith, K; Di Florio, A; Lee, P H; Bromet, E J; Buckley, P F; et al. (Translational psychiatry, 2017)
We performed a genome-wide association study of 6447 bipolar disorder (BD) cases and 12 639 controls from the International Cohort Collection for Bipolar Disorder (ICCBD). Meta-analysis was performed with prior results from the Psychiatric Genomics Consortium Bipolar Disorder Working Group for a combined sample of 13 902 cases and 19 279 controls. We identified eight genome-wide significant, associated regions, including a novel associated region on chromosome 10 (rs10884920; P =3.28 × 10 −8 ) that includes the brain-enriched cytoskeleton protein adducin 3 ( ADD3), a non-coding RNA, and a neuropeptide-specific aminopeptidase P ( XPNPEP1) . Our large sample size allowed us to test the heritability and genetic correlation of BD subtypes and investigate their genetic overlap with schizophrenia and major depressive disorder. We found a significant difference in heritability of the two most common forms of BD (BD I SNP- h 2 =0.35; BD II SNP- h 2 =0.25; P =0.02). The genetic correlation between BD I and BD II was 0.78, whereas the genetic correlation was 0.97 when BD cohorts containing both types were compared. In addition, we demonstrated a significantly greater load of polygenic risk alleles for schizophrenia and BD in patients with BD I compared with patients with BD II, and a greater load of schizophrenia risk alleles in patients with the bipolar type of schizoaffective disorder compared with patients with either BD I or BD II. These results point to a partial difference in the genetic architecture of BD subtypes as currently defined.